Economic disparity in bicycle helmet use by children six years after the introduction of legislation. Issue 4 (3rd August 2006) - Macpherson, A K; Macarthur, C; To, T M; Chipman, M L; Wright, J G; Parkin, P C
Abstract : Background: Studies evaluating the effectiveness of bicycle helmet legislation often focus on short term outcomes. The long term effect of helmet legislation on bicycle helmet use is unknown. Objective: To examine bicycle helmet use by children six years after the introduction of the law, and the influence of area level family income on helmet use. Methods: The East York (Toronto) health district (population 107 822) was divided into income areas (designated as low, mid, and high) based on census tract data from Statistics Canada. Child cyclists were observed at 111 preselected sites (schools, parks, residential streets, and major intersections) from April to October in the years 1995–1997, 1999, and 2001. The frequency of helmet use was determined by year, income area, location, and sex. Stratified analysis was used to quantify the relation between income area and helmet use, after controlling for sex and bicycling location. Results: Bicycle helmet use in the study population increased from a pre-legislation level of 45% in 1995 to 68% in 1997, then decreased to 46% by 2001. Helmet use increased in all three income areas from 1995 to 1997, and remained above pre-legislation rates in high income areas (85% in 2001). In 2001, six years post-legislation, the proportion of helmeted cyclists in mid and low income areas had returned to pre-legislation levels (50% and 33%, respectively). After adjusting for sex and location, children riding in high income areas were significantly more likely to ride helmeted than children in low income areas across all years (relative risk = 3.4 (95% confidence interval, 2.7 to 4.3)). Conclusion: Over the long term, the effectiveness of bicycle helmet legislation varies by income area. Alternative, concurrent, or ongoing strategies may be necessary to sustain bicycle helmet use among children in mid and low income areas following legislation.